1982
DOI: 10.1210/jcem-54-5-1033
|View full text |Cite
|
Sign up to set email alerts
|

Both Human Pituitary Growth Hormone and Recombinant DNA-Derived Human Growth Hormone Cause Insulin Resistance at a Postreceptor Site*

Abstract: We have investigated the effects on carbohydrate metabolism of human GH produced by recombinant DNA technology (methionyl-hGH) compared with pituitary hGH. Twelve normal adult male subjects received four daily im injections of either methionyl-hGH or pituitary hGH in a double blind, crossover study. Oral glucose tolerance tests and assays of insulin binding to peripheral monocytes were performed before th initial administration and 12 h after the fourth injection of both hGH preparations. Both methionyl-hGH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
1
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(63 citation statements)
references
References 24 publications
3
57
1
2
Order By: Relevance
“…The effect of GHT on glucose metabolism is predominantly insulin antagonistic. A marked hyperinsulinemia and a resistance to the action of insulin, as demonstrated by euglycemic clamp studies in healthy subjects, have been demonstrated [7,32]. We already demonstrated an increase in HOMA-IR, related to the increased insulin levels and without any untoward effect on glucose metabolism, in a small group of GHD children after GHT [33].…”
Section: Discussionsupporting
confidence: 55%
“…The effect of GHT on glucose metabolism is predominantly insulin antagonistic. A marked hyperinsulinemia and a resistance to the action of insulin, as demonstrated by euglycemic clamp studies in healthy subjects, have been demonstrated [7,32]. We already demonstrated an increase in HOMA-IR, related to the increased insulin levels and without any untoward effect on glucose metabolism, in a small group of GHD children after GHT [33].…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, the individual response to rhGH remains highly variable, and some effects of replacement therapy, for example, on glucose metabolism, are still a matter of debate. In fact, while it is well known that GH influences glucose homeostasis through increased lipolysis and insulin antagonism (16), low GH and IGF1 levels are associated with impaired glucose tolerance (IGT) in adults (17). Several reports have evaluated the effects of rhGH replacement on glucose metabolism in GHD adults, mostly documenting a short-term and transient deterioration of insulin sensitivity with a successive long-term stabilization, probably due to the persistent reduction in BF%, as also confirmed by a study performed by our group (18).…”
Section: Introductionmentioning
confidence: 99%
“…In studies utilizing liver membranes prepared from normal or hypophysectomized rats injected with GH [37] or monocytes isolated from acromegalic patients [38], a decreased binding capacity was offset by an increased binding affinity so that little change in total insulin binding was noted. In other studies in which GH was administered to children with hypopituitarism [39] or to normal subjects [8,40], no changes in insulin-binding capacities or affinities were observed.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, both a receptor and post-receptor defect occur. However, since subjects exposed to excess GH for short, intermittent periods of time demonstrate insulin antagonism in the face of normal insulin binding [8,39,40], we suggest that the post-receptor defect causing decreased tissue responsiveness occurs earlier and is more important in altering carbohydrate metabolism than the receptor defect causing impaired tissue sensitivity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation